2020
DOI: 10.1111/jdv.16331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of lip infantile haemangiomas and main risk factors for ulceration: an 8‐year retrospective study of 69 Chinese infants

Abstract: Background Infantile haemangiomas (IHs) involving the lip are of special concern because of the susceptibility of complications, including ulceration, obstruction and disfigurement. The available data for the relationship between their clinical characteristics and ulcerations are limited. Objectives To describe the clinical characteristics of lip IHs and to evaluate the main risk factors for ulceration. Methods A retrospective study was designed that included infants with lip IHs during an 8‐year period, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our study was limited in that the lower lip lesions (14/18) accounted for more than 70% of all eligible cases, which was probably caused by its retrospective design. However, several studies also found that lip IH occurred more commonly on the lower lip or on the mandibular segment [ 16 ], and lesions involving these sites had increased susceptibility to ulceration [ 21 ]. In our opinion, these findings can partly explain the high proportion of lower lip lesions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was limited in that the lower lip lesions (14/18) accounted for more than 70% of all eligible cases, which was probably caused by its retrospective design. However, several studies also found that lip IH occurred more commonly on the lower lip or on the mandibular segment [ 16 ], and lesions involving these sites had increased susceptibility to ulceration [ 21 ]. In our opinion, these findings can partly explain the high proportion of lower lip lesions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that the lower lip receives more friction and dipping during feeding and crying. But among untreated IHs, the prognosis of the upper lip hemangioma may be worse than the lower lip hemangioma [ 7 , 17 ]. We compared the therapeutic effect of IH in different sites of the lip after receiving the combined therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Labial region, which has a special histological structure, locates in a rubbed and immersed environment. Therefore, lip hemangioma is more likely to cause ulcer than other parts, resulting in scar, deformities, and even facial damage [ 7 ]. Lip hemangioma needs early intervention, but the best therapy is still unclear.…”
Section: Introductionmentioning
confidence: 99%